2016
DOI: 10.3390/w8070310
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Variation in Local Stormwater Infrastructure Use and Stormwater Management Paradigms over the 20th Century

Abstract: Stormwater management has significant consequences for urban hydrology, water quality, and flood risk, and has changed substantially over history, but it is unknown how these paradigm shifts play out at the local scale and whether local changes in stormwater infrastructure use follow similar trajectories across cities. This research addressed: (1) How does current infrastructure use and past infrastructure transitions vary across three cities with similar biophysical and climatic contexts but different develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…Starting in the 1970s, communities began installing stormwater control measures (SCMs) to store and treat stormwater runoff before delivering it to streams (National Research Council, ). Since the 1980s, the types and locations of SCMs installed on the landscape have shifted from large, centralized SCMs focused on storing and detaining stormwater to a wide variety of smaller capacity SCMs distributed across the watershed to manage stormwater closer to where runoff is generated (Hale, ; McPhillips & Matsler, ).…”
Section: Introductionmentioning
confidence: 99%
“…Starting in the 1970s, communities began installing stormwater control measures (SCMs) to store and treat stormwater runoff before delivering it to streams (National Research Council, ). Since the 1980s, the types and locations of SCMs installed on the landscape have shifted from large, centralized SCMs focused on storing and detaining stormwater to a wide variety of smaller capacity SCMs distributed across the watershed to manage stormwater closer to where runoff is generated (Hale, ; McPhillips & Matsler, ).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last century there has been an evolution in management of urban stormwater. Increased impervious surface area from growing cities has generated more and more runoff during storm events, leading to the development of extensive networks of underground pipes to efficiently route water away from buildings and other infrastructural systems (Kaushal et al, 2015;Hale, 2016). As these piped stormwater systems expanded, ecological research revealed the detrimental impacts of this strategy on downstream water bodies, including damaging erosion, increased flooding, and poor water quality (Walsh et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies have examined the various influences behind these transitions in concert with detailed examination of the temporal changes in implementation of particular types of SCMs. Hale (2016) highlighted differing implementation trajectories of stormwater infrastructure among three Utah cities and increasing recent implementation of GSI such as retention basins but did not delve into particular types of GSI. Here we add a comparative temporal analysis of many specific types of GSI facilities that are increasingly popular across the US.…”
Section: Introductionmentioning
confidence: 99%
“…Despite frequent, and occasionally major, flooding, the total damages from flooding in Utah over the past two decades are relatively small compared to other regions in the U.S. with larger populations and urban areas (https://www.ncdc.noaa.gov/stormevents/). However, this region has an even longer history of significant flooding, with major floods occurring in the 1940s, 1960s, and 1980s (Flores ; Lindskov ; Hale ).…”
Section: Methodsmentioning
confidence: 99%